Study of emulsifier nature effect on the process of hydrocarbon fraction cooligomerization in the emulsion - Фуч, Уляна Василівна; Дзіняк, Богдан Остапович; Субтельний, Роман Олександрович (Eastern-European Journal of Enterprise Technologies, 2015)
The process of emulsion cooligomerization of C9 fraction unsaturated hydrocarbons of cooligomers production (synthetic low-molecular petroleum resins), which are obtained from cheap petrochemical raw materials - hydrocarbon fractions of liquid pyrolysis products (LPP) or cracking of oil, refined products and gas was investigated in the paper. Since the emulsifier and initiator nature, as well as the emulsification process have the greatest effect on the cooligomerization process in the emulsion, the research is aimed at studying the influence of the main factors - the nature and concentration of emulsifiers and initiators on the yield and physicochemical properties of cooligomers obtained, namely bromine number, softening temperature, color and molecular weight. For that, surface-active properties of emulsifiers used were thoroughly studied, the surface tension isotherm for the given emulsifiers (sodium stearate and oleate, emulsifier E-30) was obtained. To determine the optimal emulsifier concentration, the critical micelle concentration (CMC) and surface tension at the point corresponding to the CMC was defined. It was found that the emulsifier amount increase to the CMC point promotes the yield enhancement (up to 17.8 wt%) and improves the physicochemical properties of the product. Based on the studies, optimal concentrations of cooligomerization components: potassium persulfate initiator - 0.1 wt%, emulsifier E-30 - 0.7 wt% were selected.